2018
DOI: 10.1002/chem.201802318
|View full text |Cite
|
Sign up to set email alerts
|

Acylation of Homoatomic Ge9 Cages and Subsequent Decarbonylation

Abstract: The direct acylation of Ge Zintl clusters by the reaction of K[Ge {Si(SiMe ) } ] with acyl chlorides in hexane or toluene solutions is presented, leading to the neutral, carbonyl-derivatized products [{Si(SiMe ) } Ge (CO)R'] (R'=Me, iPr, tBu, Ph, Bz, cyclopropylmethyl, phenethyl, 4-vinylphenyl). This reaction is applicable to a wide range of acyl chlorides and allows for diverse functionalization of Ge Zintl clusters. [{Si(SiMe ) } Ge (CO)tBu] readily releases CO at ambient conditions under formation of [{Si(S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…The broadness of these bands confirms the flexibility of the Ge 9 clusters in solution, allowing for a great number of excited states and transitions (see Figure S16, Supporting Information). Dynamic processes in solution at room temperature have already been reported for other Ge 9 cluster compounds , . The pronounced band at 209 nm is in good agreement with the absorption at 215 nm in the theoretical UV/Vis spectrum of 4a .…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The broadness of these bands confirms the flexibility of the Ge 9 clusters in solution, allowing for a great number of excited states and transitions (see Figure S16, Supporting Information). Dynamic processes in solution at room temperature have already been reported for other Ge 9 cluster compounds , . The pronounced band at 209 nm is in good agreement with the absorption at 215 nm in the theoretical UV/Vis spectrum of 4a .…”
Section: Resultssupporting
confidence: 83%
“…Since compounds 2 and 3 could not be obtained analytically pure due to fail of attempted crystallization experiments, the compounds were not used for UV/Vis measurements, even though their existence in solution was verified. Temperature‐dependent 1 H NMR studies of dissolved crystals of 1 in [D 8 ]toluene revealed dynamic processes in solution as has already been observed for other neutral Ge 9 cluster compounds (Figure ) , …”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Owing to the shielding of the [Ge 9 ] core, reactions of the tris‐silylated cluster are limited to the introduction of less bulky main group element ligands, yielding uncharged cluster compounds with Ge−C, Ge−P and Ge−Sn exo ‐cluster bonds such as [Ge 9 {Si(TMS) 3 } 3 R] [R: Et, [8] (CO) t Bu, [9] t Bu, [9] {(CH 2 ) n CH=CH 2 } ( n : 1, 3) [7c] ], [Ge 9 {Si(TMS) 3 } 3 (PRR l )] (R=R l : i Pr, Cy; [5] R: t Bu, R l : {(CH 2 ) 3 CH=CH 2 } [10] ), and [Ge 9 {Si(TMS) 3 } 3 SnR 3 ] (R: n Bu, [8] Ph [11] ). Except for the Sn‐containing species, which (partially) show multicenter Ge−Sn bonds, all main group element fragments are attached to the [Ge 9 ] entity via 2‐center‐2‐electron (2c‐2e) bonds pointing radially away from the center of the cluster.…”
Section: Methodsmentioning
confidence: 99%
“…However, solution chemistry with the more stable and better characterized [Ge 9 ] clusters is far better developed. They undergo a variety of reactions with different reagents like transition metal complexes, acyl chlorides or chlorophosphines [5,[27][28][29]. As mentioned above, the [Ge 9 ] clusters exist with three different overall charges: −4, −3 and −2.…”
Section: Introductionmentioning
confidence: 99%